Nitrogen-doped-carbon-coated hexagonal cobalt oxyhydroxide/reduced graphene oxide nanocomposite for sensitive and selective detection of nitrite in human hepatoma cells. (10th April 2019) - Cui, Xiaoqing; Yue, Chaochao; Zhu, Ruifeng; Fang, Wenhui; Wang, Jing; Zhao, Hong; Li, Zengxi
Abstract: Selective and sensitive determination of nitrite is of great importance in practical application. In the present work, a novel nitrite sensing platform was built based on the fabrication of nitrogen-doped-carbon-coated hexagonal cobalt oxyhydroxide (CN@CoOOH) on reduced graphene oxide (RGO) using zeolitic imidazolate framework (ZIF)-67 as a precursor. The CN@CoOOH/RGO nanocomposite was confirmed by UV–visible spectroscopy, Fourier transform infrared spectroscopy, x-ray photoelectron spectrum, transmission electron microscopy, scanning electron microscopy, and x-ray diffraction. We applied the nanocomposite to detect nitrite selectively and sensitively through amperometry for the first time. The anodic current values increased with the addition of nitrite. Therefore, the concentrations of nitrite were quantitatively detected using a CN@CoOOH/RGO based sensor. A wider linear range of 0.1 to 7000 μ M was obtained with a lower detection limit of 10 nM (S/N = 3). The proposed method was also applied to detect nitrite released from normal liver cells and human hepatoma cells.